Schools should still be the last to close and first to open if there were any future lockdown - Viner, R; Bonell, C; Blakemore, S-J; Hargreaves, J; Panovska-Griffiths, J (BMJ Publishing Group, 2022)
As schools in England return for the start of the new term this week, these authors argue why schools should be provided with resources to remain open amid rising covid cases.